Validity of the RP3 rowing ergometer`s mechanical power output measurement - Mentz, L.; Winkert, K.; Steinacker, J. M.; Engleder, T.; Treff, G. (Sports Engineering, 2025)
The RP3 indoor rower is used for training and testing in sports and science. The validity of its mechanical power output (power) has not been assessed. In similar rowing ergometers, the previous studies reported an underestimation of power associated with rowing inconsistency, suggesting a similar phenomenon here. We therefore aimed to evaluate the validity of power in the RP3. The design was informed by a validated motorized test rig that facilitates the systematic implementation of both steady and unsteady series of simulated rowing. This rig also incorporates a reference measurement of power, which was then compared to power of the RP3. Power was underestimated by 4.7-5.3% during a series of 50 strokes without significant differences between steady and unsteady rowing, but the random error was amplified 10- to 35-fold during unsteady rowing (± 0.3% vs. ± 3.1 to ± 10.4% depending on the design of unsteadiness). Since power of the first seven strokes was underestimated by 2-83%, exclusion of the first seven strokes decreased differences to 0.9% and 0.9 to1.7%. Power of the RP3 is acceptably accurate during steady rowing. However, the first seven start strokes are underestimated, considerably affecting the arithmetic mean of a 50-stroke series. Noteworthy, if power of RP3 is converted to a pace, the consequently low pace during the first strokes mimics the situation when accelerating a boat from standstill. Nevertheless, work per time is underestimated during the seven start strokes. We thus recommend an external measurement system to measure power when short tests (e.g., 20-s all out) are conduced and generally, if scientific accuracy is warranted.